Influence of Psychological Adjustment on Educational Researchers of Federal University of Kashere Students Gombe State - Abdullahi, Bashir; Danladi, Alhaji; Musa, Binta (Kashere Journal of Education, 2025)
Psychological adjustment refers to the process of adapting to and coping with the demand and changes of life while conducting educational research, psychological adjustment improve and maintaining emotional well-being involves developing strategies to manage stress, emotion, relationships and various challenges, the objectives of the study was to examine influence of psychological adjustment of Federal University of Kashere. Educational researchers also study how the psychological well-being of students affects the conducting of educational research. The study adopted a descriptive survey design; the population of the study involves all the 400 level students of the Federal University of Kashere faculty Education. While a sample of 100 students was selected from the population of the study, using Morgan’s (1976) scale of measurement. The instrument adopted for data collection was a self-structured questionnaire titled "psychological well-being". The questionnaire consists of two sections. Section A demands personal data of the respondents. While section B gets information on Psychological well-being. Section B consists of 5 items requesting information on psychological well-being. Collected data was analysed using mean and standard deviation to answer two research questions. The findings of the study revealed that, Psychological adjustment improves the emotional wellbeing of educational researchers. Lastly, the study recommended that, School psychologists and counsellors should focus on the educational development of students, and psychologists should focus on the well-being of students.